Non-injection-site soft tissue sarcoma in cats: outcome following adjuvant radiotherapy. Issue 8 (August 2022) - Zajc, Alenka Lavra; Harper, Aaron; Benoit, Jerome; Mason, Sarah
Objectives: Biological behaviour and treatment options of non-injection-site soft tissue sarcomas (nFISS) in cats are less well understood than in dogs. The aim of this retrospective study was to assess the outcomes of cats with nFISS following treatment with adjuvant radiotherapy. Methods: The medical records of cats with soft tissue sarcomas in locations not associated with, and histology reports not suggestive of, injection-site sarcomas were reviewed. All cats underwent adjuvant radiotherapy, either hypofractionated (32–36 Gy delivered in weekly 8–9 Gy fractions) or conventionally fractionated (48–54 Gy delivered in 16–18 3 Gy fractions) to microscopic disease. Results: In total, 18 cats were included in the study, 17 with extremity nFISS and one with facial nFISS. Nine received radiotherapy after a single surgery and nine after multiple surgeries for recurrent nFISS. Eight cats were treated with a hypofractionated protocol and 10 with a conventionally fractionated protocol. The median follow-up time was 540 days (range 51–3317 days). The tumour recurred in eight (44.4%) cats following adjuvant radiotherapy; it recurred in three (37.5%) cats following a hypofractionated protocol and in five (50%) cats following a conventionally fractionated protocol. The overall median progression-free interval (PFI) for 17/18 cats was 2748 days, while the median PFI for the 7/8 cats with recurrence was 164 days. The recurrence for one cat was reported, but the date was unknown and it was therefore censored from these data. When stratifying based on the protocol, the median PFI for hypofractionated and conventionally fractionated protocols was 164 days and 2748 days, respectively. Statistically, there was no significant difference between the two protocols ( P = 0.636). Conclusions and relevance: Adjuvant radiotherapy resulted in good long-term tumour control in 12/18 cats with nFISS. Further studies in larger populations are required to assess the significance of radiation dose and fractionation on tumour control and the effect of multiple surgeries prior to initiation of radiotherapy on outcome.